#TITLE_ALTERNATIVE# - Octaviano (nim: 101 03 019), Andrew
Abstract: The modeling of gas flow through the pipe transmission is often done using an assumption that the flow is in a steady state, the condition for which the gas flow doesnt change in time. However, there are some situation for which this assumption is not reliable anymore. In this condition, we apply the transient gas flow model. By neglecting the effect of temperature, the transient gas flow model is comprised of continuity and momentum equations, together with the equation of state which uses some assumptions in order to simplify the problem. From these equations, we derive the pipeline equations which describe the distributions of pressures and gas flow rates at all time. To solve the pipeline equations numerically, the finite difference methods combined with Runge Kutta methods are used. The problem will next be extended to a pipeline junction, as a benchmark for the pipeline network. At the junction, we shall apply the Kirchoff Law. Then, the Newton Raphson method will be used in order to determine the pressure at the junction. To justify the model, simulations with hypothetical data are also provided.